Pemberdayaan Pengrajin Emas “Surianti Gold” - I Wayan Gede Lamopia; Puspawan, Dewa K Hendra; Borbon , I Made Wahyu; Baskara , I Made Arya Basma (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Surianti Gold is one of the gold craftsmen in Batubulan Village, located at Br. Tegal Jaya. Ni Wayan Surianti as the owner and gold craftsman has been in business since 1998. For 25 years, Mrs Surianti has been involved in making gold jewellery creations such as sumpel, pendant, cross, and also accept orders according to customer requests. Suranti Gold's production process still uses manual equipment. Even though there are many gold craftsmen in the Batubulan area who use modern tools. To support Surianti Gold gold craftsmen to be independently competitive, community service activities are carried out that focus on partner problems, namely production management and brand identity. This activity was carried out for 8 months by applying the pre-implementation, implementation and evaluation methods. The results of this community service activity are to improve production management, namely that the partner has a magnetic tumbler machine production tool which so far he still uses gold washing services. In addition, to optimise financial records, notes are given and to increase social networks, brand identity is given through the packaging logo. Overall, the activity was carried out with good cooperation.